Evaluating student perspectives on understanding of complex systems - Barker, Stephen G. (The International Academic Forum (IAFOR), 2022)
Advances in technological detail and sophistication have resulted in more complex products, systems and services which can be more difficult for individuals to conceptualise and understand. This eventuality has potential to increase risks and assumptions in the use, operation, and management over time of such products and therefore presents a growing problem for those who have to plan and undertake such activities. It can thus be seen as important that people are informed as to the possible ramifications of increased complexity, and this presents a challenge to educators in terms of how the notion of ever-increasing complexity can be taught and inculcated. Previous work has considered how this might be achieved, evaluating learner preferences, mechanisms to describe greater complexity and its effects, and teaching strategies which can facilitate that learning and understanding. This paper builds upon the earlier work in the light of having since delivered complex systems course content at masters level. By viewing the situation through the prism of student learning experience and using informal discussion with learners and formal feedback on factors such as comprehension of topic, ability to analyse and evaluate holistically, and capability to apply understanding to real-life business scenarios, this paper assesses areas that students perceived as difficult or challenging to explicate and actualise. This is then placed in the overall context of the course cohort to analyse trends and whether different students experienced problems with the same issues before suggesting a revised andragogical strategy to address issues and improve the student learning experience.
Keywords: Andragogy; Supporting Students; Systems Engineering; Complex Systems